2011
DOI: 10.1016/j.jvs.2011.06.115
|View full text |Cite
|
Sign up to set email alerts
|

Great saphenous vein patency and endovenous heat-induced thrombosis after endovenous thermal ablation with modified catheter tip positioning

Abstract: In patients undergoing RFA for saphenous reflux, neither catheter tip positioning nor vein diameter correlates with the length of the proximal patent segment of GSV after ablation. In addition, catheter positioning does not decrease the incidence of proximal thrombus extension into the femoral vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
2
29
2
Order By: Relevance
“…We also agree with Haqqani et al [35] that the catheter must be advanced under direct DUS visualization to the saphenofemoral region. Blind positioning of the catheter must be avoided, as well as the advancement of the catheter into the femoral vein before it was positioned in the proximal GSV, as all these factors play an important role in preventing EHIT and DVT.…”
Section: Discussionsupporting
confidence: 92%
“…We also agree with Haqqani et al [35] that the catheter must be advanced under direct DUS visualization to the saphenofemoral region. Blind positioning of the catheter must be avoided, as well as the advancement of the catheter into the femoral vein before it was positioned in the proximal GSV, as all these factors play an important role in preventing EHIT and DVT.…”
Section: Discussionsupporting
confidence: 92%
“…For this reason, some authors advise keeping a distance of approximately 2 cm from the confluence to prevent intimal damage at the SFJ, which can provoke a heat-induced thrombus or deep venous thrombosis. 16 In accordance with our study protocol, the distance from the SFJ was kept between 1.5 and 2 cm. Our previous publication on 1-year post-treatment results reported that heat-induced thrombus at the SFJ was observed on DUS in 3 patients (5%) 1 week after EVLA.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite the variability of treatment regimens for EHIT, the reported rates of occlusive DVT and PE following endovenous ablation of the GSV remain low. [9][10][11][12] EHIT displays a distinct sonographic echogenicity compared with spontaneous acute DVT, and its natural history appears to be less prone to develop thrombus progression and extension. 13 Despite these differences, EHIT progression to PE has been reported in the literature and may result in life-threatening complications if not properly identified and treated.…”
Section: Discussionmentioning
confidence: 99%